Effects of a Single Dose of a Creatine-Based Multi-Ingredient Pre-workout Supplement Compared to Creatine Alone on Performance Fatigability After Resistance Exercise: A Double-Blind Crossover Design Study - Negro, Massimo; Cerullo, Giuseppe; Perna, Simone; Beretta-Piccoli, Matteo; Rondanelli, Mariangela; Liguori, Giorgio; Cena, Hellas; Phillips, Stuart M.; Cescon, Corrado; D’Antona, Giuseppe (Frontiers in Nutrition, 2022)
Background: The aim of this study was to investigate the acute effects of a single oral administration of a creatine-based multi-ingredient pre-workout supplement (MIPS) on performance fatigability and maximal force production after a resistance exercise protocol (REP). Methods: Eighteen adult males (age: 23 ± 1 years; body mass: 76.4 ± 1.5 kg; height: 1.77 ± 1.52 m) were enrolled in a randomized, double-blind, crossover design study. Subjects received a single dose of a MIPS (3 g of creatine, 2 g of arginine, 1 g of glutamine, 1 g of taurine and 800 mg of β-alanine) or creatine citrate (CC) (3 g of creatine) or a placebo (PLA) in three successive trials one week apart. In a randomized order, participants consumed either MIPS, CC or PLA and performed a REP 2h later. Before ingestion and immediately after REP, subjects performed isometric contractions of the dominant biceps brachii: two maximal voluntary contractions (MVCs), followed by a 20% MVC for 90 s and a 60% MVC until exhaustion. Surface electromyographic indices of performance fatigability, conduction velocity (CV) and fractal dimension (FD), were obtained from the surface electromyographic signal (sEMG). Time to perform the Task (TtT), basal blood lactate (BL) and BL after REP were also measured. Results: Following REP, statistically significant (p<0.05) pre-post mean differences between MIPS and PLA were observed for ⧍TtT, ⧍CV slopes (20% MVC) and ⧍CV slopes (60% MVC). A pairwise comparison analysis showed no consistent statistically significant differences in other variables between groups. Conclusion: After REP, a creatine-enriched MIPS resulted in greater improvement of sEMG descriptors of performance fatigability and TtT compared to CC alone.